Supported monatomic / nanocluster composite noble metal catalyst as well as preparation method and application thereof
The supported single-atom/nano cluster composite catalyst is prepared by coordination complex coupling thermal shock method and sol impregnation method, which solves the problems of complex preparation steps and low support universality in the prior art, and achieves high activity and structural stability of the catalyst in CO oxidation reaction.
Patent Information
- Application Number
- CN202411885650.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the prior art, the preparation steps of the supported precious metal catalyst are complex, the equipment requirements are high, and secondary heat treatment and reduction steps are required, which makes it difficult for the precious metals to maintain the structural stability, the dispersion scale is difficult to control in proportion, and the universality of the support is low.
Coordination complex coupled thermal shock method is used to load single atoms, and nanoclusters are loaded through sol impregnation method to avoid secondary heat treatment and reduction steps, and the proportional regulation of single atoms and nanoclusters is achieved.
The prepared catalyst exhibits higher oxidation performance in CO oxidation reaction and has universal support. It is suitable for oxide and carbon support. It has a simple preparation process, low cost and stable catalyst structure.
Smart Images

Figure CN119701946A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a supported single atom / nano cluster composite noble metal catalyst and a preparation method and application thereof. Background Art
[0002] Supported noble metal catalysts have been widely studied and applied due to their high activity, selectivity and stability in many reactions. In previous studies, researchers have been committed to dispersing noble metals to nanometers (2-10nm), sub-nanometers (<2nm) and even single atoms to improve the effective utilization of metal atoms and the reaction rate per unit active site. In some catalytic reactions, especially when two or more molecules are involved in adsorption and activation, a single dispersed active species often cannot meet the requirements of simultaneous adsorption and activation of multiple molecules. Therefore, in recent years, single atom and nanoparticle composite catalysts have begun to receive attention and research. For example, the following literature discloses research content:
[0003] 1) The document J.Am.Chem.Soc.2023,145,9540 reports a laser ablation strategy to prepare a catalyst in which single atoms and nanoparticles coexist for CO oxidation. Laser irradiation provides the ability for Pt nanoparticles to be redispersed, and some Pt particles are dispersed into single atoms, achieving full CO conversion at 250°C in the CO oxidation reaction.
[0004] 2) Literature J.Am.Chem.Soc.2024,146,35,24440 prepared Pd single atoms by ion exchange and Pd nanoclusters by photodeposition method for photocatalytic methanol dehydrogenation reaction.
[0005] 3) In the literature J.Energy Chem.2023,79,535, single-atom Co and highly dispersed nanoparticle Co dual-sized MOF-derived Co catalysts were prepared by in situ evaporation method for cascade demethoxylation and dearomatization of lignin-derived o-methoxyphenol to cyclohexanol.
[0006] However, the methods disclosed in the above documents have the following technical problems: the preparation steps of the catalyst are relatively complicated, the equipment requirements are relatively high, and generally more than two heat treatments are required. It is difficult for the precious metal in the catalyst to maintain structural stability, making it difficult to synthesize the dispersion scale in a controlled manner in proportion, and the universality of the carrier is not high. Some methods are only applicable to oxide carriers and some are only applicable to carbon carriers. Therefore, it is particularly urgent to develop a method for preparing a single-atom and nanoparticle composite catalyst with universal carrier, controllable single-atom / nanoparticle ratio, stable structure, mild preparation conditions, and environmental friendliness. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a method for preparing a supported single atom / nano cluster composite catalyst, which has the characteristics of universal carrier and controllable single atom / nano cluster ratio. First, single atoms are loaded by ligand complex coupling thermal shock method, and then nano clusters are loaded by sol impregnation method. Since H2 is used for thermal shock to obtain a single atom-dispersed catalyst during the preparation process, and nano clusters are obtained by alcohol-base reduction, secondary heat treatment and reduction steps are avoided, and single atoms and nano clusters in the catalyst are synthesized in proportion, and the structure is stable. Another technical problem solved by the present invention is that the single atom / nano cluster composite catalyst obtained by the preparation method of the present invention shows higher oxidation performance than pure single atoms and pure nano clusters in CO oxidation reaction. Compared with the prior art, the preparation process of the present invention is simple, does not require secondary heat treatment and reduction treatment, is conducive to the synthesis of single atoms and nano clusters in the catalyst in proportion, and has good carrier universality, and oxide carriers and carbon carriers are applicable.
[0008] The catalyst in the present invention is a single atom / nanocluster composite catalyst, wherein the ratio of single atoms in the single atom / nanocluster can be adjusted in the range of 10 to 90%, and the particle size of the nanocluster is controlled at 1 to 2 nm. In terms of preparation method, the single atom catalyst is loaded with single atoms by a coordination complex coupling thermal shock method, and the nanocluster is loaded by a sol impregnation method.
[0009] The technical solution adopted by the present invention is as follows:
[0010] A method for preparing a supported noble metal catalyst, in which the active component noble metal coexists in the form of single atoms and nanoclusters, and the ratio of single atoms to nanoclusters is controllable, comprising the following steps:
[0011] 1) dissolving a precursor of the noble metal M in deionized water, adding an organic complexing agent, stirring for complexing reaction, and obtaining a noble metal M precursor complex solution;
[0012] 2) adding a carrier to the solution in step 1), stirring sufficiently to load the complex on the carrier, filtering and drying, and placing the obtained solid product in a Joule ultrafast heating device in a H2 atmosphere for rapid thermal shock to obtain a single atom catalyst;
[0013] 3) loading the noble metal M nanocluster sol on the single atom catalyst in step 2) by a sol impregnation method to obtain a catalyst in which single atoms and nanoclusters of the noble metal M coexist;
[0014] The noble metal M is at least one of Pt, Rh, Ir, Ru and Pd;
[0015] The molar amount of the single atoms of the noble metal M in the catalyst accounts for 10-90% of the total amount of the single atoms and nanoclusters of the noble metal M;
[0016] The loading amount of the noble metal M in the catalyst is 0.1-1%.
[0017] Furthermore, the organic complexing agent in step 1) is at least one of ethylenediamine, sodium ethylenediaminetetraacetate, triethylamine, monoethanolamine, diethylenetriamine, and tetraethylenepentamine, and the molar amount of the organic complexing agent is (5 to 20)×10 of the molar amount of the noble metal M precursor. 3 times; step 1) the temperature of the stirring complex reaction is room temperature, and the reaction time is 1 to 5h.
[0018] Furthermore, in step 2), the carrier is CeO2, TiO2 or MnO2, FeO x At least one of metal oxides and carbon carriers such as activated carbon and carbon nanotubes, preferably CeO2 or TiO2, and the stirring time of step 2) is 2 to 10 hours.
[0019] Furthermore, the rapid thermal shock in step 2) is performed by Joule ultrafast heating, rapidly heating to a heat treatment temperature of 500-800° C. within 500 milliseconds, with a heat treatment time of 10-600 seconds, and then naturally cooling to room temperature.
[0020] Furthermore, the heat treatment temperature is 550-650° C., and the heat treatment time is 20-60 seconds.
[0021] Furthermore, the specific steps of step 3) are: diluting the nanocluster sol of the precious metal M with ethylene glycol, and dropping the resulting solution into the single atom catalyst while stirring evenly; then immersing at room temperature for 10 to 20 hours, and then drying the sample in a vacuum oven, and drying under vacuum to evaporate the solvent, thereby obtaining a catalyst in which single atoms and nanoclusters of the precious metal M coexist.
[0022] Furthermore, the molar amount of the single atoms of the noble metal M in the catalyst accounts for 10 to 50% of the total amount of the single atoms of the noble metal M and the nanoclusters, preferably 10 to 30%.
[0023] Furthermore, the loading amount of the noble metal M in the catalyst is 0.1 to 0.5%.
[0024] The invention also discloses the application of the supported noble metal catalyst with controllable single atom / nano cluster ratio in catalyzing CO oxidation reaction.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) The present invention adopts the coordination complex coupling thermal shock method-sol impregnation method to load single atoms and nanoclusters on the carrier respectively, and successfully prepares a catalyst in which single atoms and nanoclusters coexist. The preparation method does not undergo secondary heat treatment, which is conducive to maintaining the stability of the single atom and nanocluster structure in the catalyst, and the preparation method is easy to control, the preparation conditions are mild, the carrier is universal, the synthesis equipment requirements are low, and the preparation cost is reduced. It is applied to the CO oxidation reaction with excellent activity.
[0027] 2) The catalyst prepared by the coordination complex coupled thermal shock method-sol impregnation method adopted in the present invention realizes noble metal reduction during the preparation process without the need for other reduction steps, thereby ensuring that the proportion of single atoms and nanoclusters in the catalyst is controllable and the structure is stable.
[0028] 3) The preparation process of the catalyst of the present invention is simple, requiring only one step of heat treatment, which can ensure that the single atoms / nanoclusters in the catalyst are synthesized in a controlled proportion, and the size of the nanoclusters is evenly distributed at 1 to 2 nm. In the CO oxidation reaction, the highest oxidation performance is exhibited when the ratio of single atoms to nanoclusters is 4:1. The preparation method of the present invention can accurately control the ratio of single atoms to nanoclusters according to the specific reaction, thereby realizing the preparation of a highly active catalyst.
[0029] 4) The catalyst of the present invention can achieve complete conversion of CO at a lower temperature, which not only has low energy consumption and good catalytic reaction safety, but also helps to avoid carbon deposition of the catalyst at high temperature or oxidation deactivation of platinum species, thereby greatly improving the service life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 0.02Pt10.08Pt prepared in Example 1 and Comparative Examples 1 and 2 of the present invention NP / CeO2, 0.1Pt1 / CeO2 and 0.1Pt NP / CeO2 catalyst CO oxidation reaction performance test diagram.
[0031] Figure 2 This is a test diagram of the CO oxidation reaction performance of catalysts with different ratios of single atoms and nanoclusters prepared in Example 1 and Examples 2-6 of the present invention.
[0032] Figure 3 0.02X10.08X prepared by different precious metals prepared in Examples 1, 7-10 of the present invention NP / CeO2 (X is Pt, Rh, Ir, Ru, Pd) catalyst CO oxidation reaction performance test diagram.
[0033] Figure 4 0.02Pt10.08Y prepared in Examples 1, 11-14 of the present inventionNP / CeO2 (Y is Pt, Rh, Ir, Ru, Pd) catalyst CO oxidation reaction performance test diagram.
[0034] Figure 5 This is a test diagram of the CO oxidation reaction performance of catalysts with different Pt loadings prepared in Examples 1, 15, and 16 of the present invention.
[0035] Figure 6 This is a test chart of CO oxidation reaction performance of different supported catalysts prepared in Examples 1, 17, 18 and 19 of the present invention.
[0036] Figure 7 This is a test diagram of the CO oxidation reaction performance of the catalyst prepared in Example 1 and Comparative Example 3 of the present invention.
[0037] Figure 8 This is a test diagram of the CO oxidation reaction performance of the catalysts prepared in Example 1 and Comparative Example 4 of the present invention.
[0038] Fig. 9 AC-HAADF-STEM electron microscope images of the catalysts prepared in Example 1(a), Comparative Example 1(b) and Comparative Example 2(c) of the present invention (the red circles are Pt nanoclusters and the yellow circles are Pt single atoms).
[0039] Fig.10 0.02Pt10.08Pt prepared in Example 1 NP / CeO2 catalyst CO oxidation reaction stability performance test diagram. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0041] Example 1: 0.02Pt10.08Pt NP / CeO2 catalyst preparation:
[0042] (1) Preparation of single-atom Pt1 / CeO2 catalyst by coordination complex coupling thermal shock method: 27 μL of H2PtCl6 aqueous solution with a Pt element concentration of 7.46 mg / mL was measured and added to 50 mL of deionized water for dilution. 1.0 g of ethylenediamine reagent was added and stirred for 3 h. Then 1.0 g of CeO2 was added and stirred for 5 h. The catalyst precursor was placed in a vacuum oven at 80 °C and dried for 12 h to obtain the catalyst precursor. The catalyst precursor was then placed in a Joule ultrafast heating device and heated under a flowing stream of 30 mL min -1 In a pure hydrogen atmosphere, the catalyst was heated from room temperature to 600°C within 200 milliseconds. After heat treatment for 30 seconds, it was naturally cooled to room temperature to obtain a Pt1 / CeO2 catalyst with a Pt single atom load of 0.02 wt%.
[0043] (2) Preparation of precious metal sol by alcohol-base reduction method: Taking Pt sol as an example, Pt sol was prepared by ethylene glycol reduction method. A certain amount of chloroplatinic acid ethylene glycol solution and an appropriate amount of sodium hydroxide ethylene glycol solution were mixed in a three-necked flask, and then reduced in an inert atmosphere at an oil bath temperature of 160°C to obtain Pt sol: Specifically, 1 g H2PtCl6·6H2O was dissolved in 50 mL ethylene glycol, and 50 mL of 0.25 mol L -1 The sodium hydroxide ethylene glycol solution was stirred at room temperature for 1 hour and then moved into a 160°C oil bath. The mixture was stirred under argon atmosphere for 1 hour to obtain a dark brown transparent Pt sol (Pt mass concentration 3.76 mg mL -1 ).
[0044] (3) Sol impregnation method for loading nanoclusters: Weigh 1 g of single-atom Pt1 / CeO2 catalyst dried in a 120°C oven for 2 h into a 20 mL beaker, measure 213 μL of Pt sol with a Pt element concentration of 3.76 mg / mL, add 2 mL of ethylene glycol to dilute, and then drop it into the Pt1 / CeO2 catalyst while stirring evenly; then impregnate at room temperature for 12 h, and then dry the sample in a 120°C vacuum oven for 12 h to obtain a catalyst 0.02Pt10.08Pt in which single-atom Pt and nanocluster Pt coexist. NP / CeO2, the total Pt loading of the catalyst is 0.1wt%.
[0045] Embodiment 2-6:
[0046] The preparation method of the catalyst of Example 2-6 is the same as that of Example 1, the only difference being that the added volume of the H2PtCl6 aqueous solution in step (1) and the added volume of the Pt sol in step (3) are changed, while the other conditions remain unchanged, so that the total Pt loading of the catalyst of Example 2-6 remains unchanged at 0.1wt%, while the ratio of Pt single atoms and nanoclusters changes.
[0047] See Table 1 for the specific volumes of H2PtCl6 aqueous solution and Pt sol added during the catalyst preparation process of Examples 2-6, as well as the ratios of single atoms and nanoclusters of Pt in the catalyst.
[0048] Table 1
[0049]
[0050] Embodiment 7-10:
[0051] The preparation method of the catalyst of Examples 7-10 is the same as that of Example 1, except that the type of precious metal is different, the mass of the precious metal element in step (1), step (2), and step (3) remains unchanged, and the other conditions remain unchanged. The total loading of the precious metal element of the catalyst of Examples 7-10 remains unchanged at 0.1wt%, and the ratio of single atoms and nanoclusters of the precious metal remains unchanged.
[0052] The types of precious metals, single atom precursors and nanoclusters in the catalyst preparation process of Examples 7-10 are shown in Table 2.
[0053] Table 2
[0054]
[0055] Examples 11-14: The catalyst preparation process is the same as Example 1, except that the type of precious metal nanocluster in the catalyst preparation is changed, the mass of the precious metal element in step (2) and step (3) remains unchanged, and the other conditions remain unchanged. The total loading of the precious metal element in the catalyst of Examples 11-14 remains unchanged at 0.1wt%, and the ratio of single atoms and nanoclusters of the precious metal remains unchanged. The specific conditions for changing the type of precious metal nanocluster are shown in Table 3.
[0056] Table 3
[0057]
[0058]
[0059] Examples 15-16: The catalyst preparation method is the same as Example 1, except that the volume of the H2PtCl6 aqueous solution added in step (1) and the volume of the Pt sol added in step (3) are changed, and the other conditions remain unchanged, so that the total Pt loading of the catalyst is changed. The specific condition changes are shown in Table 4.
[0060] Table 4
[0061]
[0062] Examples 17-19: The catalyst preparation method is the same as Example 1, the only difference is that the catalyst carrier is different, and the other conditions remain unchanged. The specific changes in the catalyst carrier are shown in Table 5.
[0063] Table 5
[0064]
[0065] Comparative Example 1: A single-atom dispersed 0.1Pt1 / CeO2 catalyst was prepared by a coordination complex coupled thermal shock method, wherein the Pt loading was 0.1wt%. The specific steps were as follows: 134μL of an H2PtCl6 aqueous solution with a Pt element mass concentration of 7.46mg / mL was taken as a Pt source, added to 50mL of deionized water for dilution, 1.0g of ethylenediamine reagent was added, stirred for 3h, and then 1.0g of CeO2 was added, stirred for 5h, filtered and washed, placed in a vacuum oven at 80°C, dried for 12h to obtain a catalyst precursor, and then placed the precursor in a Joule ultrafast heating device under a flowing 30mL min -1 In a pure hydrogen atmosphere, the catalyst was heated from room temperature to 600°C within 200 milliseconds. After heat treatment for 30 seconds, it was naturally and rapidly cooled to room temperature to obtain a 0.1Pt1 / CeO2 catalyst with a Pt single atom load of 0.1wt%.
[0066] Comparative Example 2: Preparation of 0.1Pt by Sol-Gel Impregnation Method NP / CeO2 catalyst, wherein the Pt loading amount is 0.1wt%, and the specific steps are as follows: weigh 1g of CeO2 dried in a 120℃ oven for 2h and put it in a 20mL beaker, measure 266μL of Pt sol with a Pt element concentration of 3.76mg / mL (for the preparation of Pt sol, see step (2) of Example 1), add 2mL of ethylene glycol to dilute it, and then drop it into CeO2 while stirring evenly; then immerse it at room temperature for 12h, and then dry the sample in a 120℃ vacuum oven for 12h to obtain 0.1Pt NP / CeO2 catalyst.
[0067] Comparative Example 3: The preparation process is the same as that of Example 1. Compared with Example 1, the difference is that the Pt single atom load is prepared by a tubular furnace heating method. The specific steps are: 27 μL of H2PtCl6 aqueous solution with a Pt element concentration of 7.46 mg / mL is taken as a Pt source, added to 50 mL of deionized water for dilution, 1.0 g of ethylenediamine reagent is added, stirred for 3 h, and then 1.0 g of CeO2 is added, stirred for 5 h, filtered and washed, placed in a vacuum oven at 80°C, and dried for 12 h to obtain a catalyst precursor, which is placed in a tubular furnace under a flowing 30 mL min -1 In a H2 atmosphere, the temperature was raised from room temperature to 600°C at a rate of 10°C / min. The heating was terminated after 30 seconds of heat treatment, and the mixture was naturally cooled to room temperature. The subsequent steps were consistent with the steps (2) to (3) of Example 1 to obtain 0.02Pt10.08Pt NP / CeO2-Tube catalyst.
[0068] Comparative Example 4: The specific preparation method of the catalyst is the same as that of Example 1, except that "ethylenediamine reagent is not added in step (1)", and the other conditions remain unchanged. The final catalyst is marked as 0.02Pt10.08Pt NP / CeO2-without complexing agent, in which the Pt loading amount is 0.1wt%.
[0069] Application examples:
[0070] In order to evaluate the catalytic performance of the prepared catalyst, the catalyst was tested for CO oxidation reaction performance. A fixed bed reactor was used, 60-100 mg of catalyst was weighed and loaded into a U-shaped reaction tube, and the flow rate was 30 mL min -1 The reaction gas composition is 1vol%CO+1vol%O2, Ar is the balance gas, and the mass space velocity is 1.8×10 4 ~3.0×10 4 mL·g cat -1 h -1 , record the peak areas of CO, O2, and CO2 at the outlet of the chromatographic detection reactor. The calculation method of CO conversion rate is as follows:
[0071] CO Conversion (%) = ([CO] in -[CO] out ) / [CO] in ×100%;
[0072] Where: [CO] in is the chromatographic peak area corresponding to the reactor inlet CO;
[0073] [CO] out is the chromatographic peak area corresponding to CO at the reactor outlet at different reaction temperatures.
[0074] The CO oxidation reaction performance evaluation conditions are as follows: flow rate is 30 mL min -1 The gas composition is 1vol%CO+1vol%O2, Ar is the balance gas, and the mass space velocity is 1.8×10 4 mL·g cat -1 h -1 During the evaluation of CO oxidation reaction performance, the catalyst was subjected to a programmed temperature activity test. The test temperature range was 20-200°C, the starting temperature was 20°C, and each temperature was maintained for 20 minutes. Samples were collected for analysis, and then the temperature was adjusted at 2°C min. -1 The temperature is raised to the next temperature evaluation point at a rate of
[0075] The catalyst stability evaluation conditions are: flow rate 30 mL min -1, the reaction temperature is 120℃, the gas composition is 1vol%CO+1vol%O2, Ar is the balance gas, and the mass space velocity is 3.0×10 4 mL·g cat -1 h -1 .
[0076] The CO oxidation reaction performance test comparison results of the catalysts of Example 1 of the present invention and Comparative Examples 1 and 2 are shown in Figure 1 , Figure 1 The results show that the CO conversion rate on 0.1Pt1 / CeO2 catalyst is below 50% in the temperature range of 20-200℃, which is low. NP / CeO2 catalyst, the CO conversion rate was only 38.3% at 140℃, and reached 100% at 160℃; 0.02Pt10.08Pt NP / CeO2 catalyst has the best activity, with a CO conversion rate of 29% at 20℃ and full CO conversion at 120℃.
[0077] The CO oxidation reaction performance test comparison results of the catalysts of Example 1 and Examples 2-6 of the present invention are shown in Figure 2 , Figure 2 It shows that when the ratio of single atoms to nanoclusters is 4:1, that is, 0.08Pt10.02Pt NP / CeO2 catalyst, CO full conversion was not achieved in the temperature range of 20-200 °C; when the ratio of single atoms to nanoclusters was 7:3, that is, 0.07Pt10.03Pt NP / CeO2 catalyst, CO oxidation activity was improved; when the ratio of single atoms to nanoclusters was 1:1, the CO oxidation activity was improved in 0.05Pt10.05Pt NP / CeO2 catalyst, CO can be completely converted at 200℃; further increasing the ratio of Pt clusters, that is, the ratio of single atoms to nanoclusters is 1:4, at 0.02Pt10.08Pt NP / CeO2, the CO full conversion temperature was reduced to 120°C; when the Pt cluster ratio was increased to 90%, that is, when the ratio of single atoms to nanoclusters was 1:9, the CO oxidation activity decreased, and the CO full conversion temperature was 140°C; this result shows that when the nanocluster ratio was 80% (0.02Pt10.08Pt NP / CeO2), which has the best catalytic oxidation effect and significantly improved CO oxidation performance, indicating that single atoms and nanoclusters have a synergistic effect in the CO oxidation process.
[0078] The CO oxidation reaction performance test comparison results of the catalysts of Examples 1, 7-10 of the present invention are shown in Figure 3 , Figure 3The results show that the single-atom catalyst was prepared by the coordination complex coupled thermal shock method of the present invention, and then the clusters were loaded by the sol impregnation method to obtain a series of catalysts 0.02X10.08X NP / CeO2 (Rh, Pd, Ir, Pt, Ru), in the CO oxidation reaction, the activity order is 0.02Pt10.08Pt NP / CeO2>0.02Rh10.08Rh NP / CeO2>0.02Ir10.08Ir NP / CeO2>0.02Ru10.08Ru NP / CeO2>0.02Pt10.08Pd NP / CeO2, indicating that the Pt-based catalyst has higher CO oxidation performance.
[0079] The CO oxidation reaction performance test comparison results of the catalysts of Examples 1 and 11-14 of the present invention are shown in Figure 4 , Figure 4 The results show that Y NP (Y is Rh, Pd, Ir, Pt, Ru), the order of CO oxidation catalytic performance is 0.02Pt10.08Pt NP / CeO2>0.02Pt10.08Rh NP / CeO2>0.02Pt10.08Ir NP / CeO2>0.02Pt10.08Ru NP / CeO2>0.02Pt10.08Pd NP / CeO2, indicating that in the CO oxidation reaction, the synergistic effect of single atomic Pt and nanocluster Pt is the best.
[0080] The CO oxidation reaction performance test comparison results of the catalysts of Examples 1, 15 and 16 of the present invention are shown in Figure 5 , Figure 5 The results show that the ratio of single atoms to nanoclusters is kept at 4:1, and the total Pt loading is changed from 0.002Pt to 10.008Pt NP / CeO2 catalyst, CO conversion was not completely achieved in the temperature range of 20-200°C. When the total Pt loading was increased to 0.5wt%, that is, 0.1Pt10.4Pt NP / CeO2 catalyst, full CO conversion can be achieved at 40℃.
[0081] The CO oxidation reaction performance test comparison results of the catalysts of Examples 1, 17, 18 and 19 of the present invention are shown in Figure 6 , Figure 6The results show that Pt single atom and nanocluster coexistence catalysts loaded with different carriers (MnO2, TiO2, CNT) were prepared by the method of the present invention, and it was found that all of them had high CO oxidation performance, indicating that the catalyst preparation method of the present invention has universal applicability.
[0082] The CO oxidation reaction performance test comparison results of the catalysts of Example 1 and Comparative Example 3 of the present invention are shown in Figure 7 . Figure 7 The results show that compared with the 0.02Pt10.08Pt prepared in Example 1 NP / CeO2 catalyst compared to the 0.02Pt10.08Pt prepared in Comparative Example 3 NP The catalytic performance of the CeO2-Tube catalyst in the CO oxidation reaction is significantly reduced, and CO can only be completely converted at 180°C, which further illustrates the excellent performance of the catalyst prepared by the method of the present invention.
[0083] The CO oxidation reaction performance test comparison results of the catalysts of Example 1 and Comparative Example 4 of the present invention are shown in Figure 8 . Figure 8 The results show that compared with 0.02Pt10.08Pt in Example 1 NP Compared with the 0.02Pt10.08Pt / CeO2 catalyst without adding complexing agent, NP The catalytic performance of the CeO2-free catalyst in the CO oxidation reaction was significantly reduced, and the complete conversion of CO was not achieved within the tested temperature range, indicating that the addition of organic complexing ligands was conducive to the formation of Pt single atoms, which synergized with the Pt clusters in the catalyst to promote CO oxidation.
[0084] The AC-HAADF-STEM images of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown in Fig. 9 Figures a, b and c of the graph. Fig. 9 The results show that if Fig. 9 As shown in Figure a, at 0.02Pt10.08Pt NP On the / CeO2 catalyst, the dispersion of Pt nanoclusters and Pt single atoms can be observed simultaneously; Fig. 9 As shown in sub-figure b, on the 0.1Pt1 / CeO2 catalyst, Pt is highly dispersed on the carrier in the form of single atoms, without the appearance of clusters or nanoparticles; Fig. 9 As shown in Figure c, at 0.1Pt NP On the / CeO2 catalyst, Pt is dispersed in the form of nanoclusters, and no single Pt atoms are observed. Fig. 9 In Figure a, the diameter of a single Pt atom is less than 0.1 nm, and the diameter of a Pt nanocluster is about 2 nm.
[0085] The CO oxidation reaction stability performance test results of Example 1 of the present invention are shown in Fig.10 . Fig.10 The results show that 0.02Pt10.08Pt NP / CeO2 catalyst at high space velocity 3.0×10 4 mL·g cat -1 h -1 It showed good stability within 24 hours and the conversion rate was stable at about 80%.
Claims
1. A method for preparing a supported noble metal catalyst, characterized in that The active component noble metal in the catalyst coexists in the form of single atoms and nanoclusters, and the ratio of single atoms to nanoclusters is controllable, comprising the following steps: 1) Dissolving the precursor of the noble metal M in deionized water, adding an organic complexing agent, stirring for complexing reaction, and obtaining a noble metal M precursor complex solution; 2) adding a carrier to the solution in step 1), stirring sufficiently to load the complex on the carrier, filtering and drying, and placing the obtained solid product in a Joule ultrafast heating device in a H2 atmosphere for rapid thermal shock to obtain a single atom catalyst; 3) loading the noble metal M nanocluster sol on the single atom catalyst in step 2) by a sol impregnation method to obtain a catalyst in which single atoms and nanoclusters of the noble metal M coexist; The noble metal M is at least one of Pt, Rh, Ir, Ru and Pd; The molar amount of the single atoms of the noble metal M in the catalyst accounts for 10-90% of the total amount of the single atoms and nanoclusters of the noble metal M; The loading amount of the noble metal M in the catalyst is 0.1 ~ 1%.
2. The method for preparing a supported noble metal catalyst with a controllable single atom / nanocluster ratio as claimed in claim 1, characterized in that The organic complexing agent in step 1) is at least one of ethylenediamine, sodium ethylenediaminetetraacetate, triethylamine, monoethanolamine, diethylenetriamine, and tetraethylenepentamine, and the molar amount of the organic complexing agent is (5-20)×10 of the molar amount of the noble metal M precursor. 3 times; step 1) the temperature of the stirring complex reaction is room temperature, and the reaction time is 1 to 5 h.
3. The method for preparing a supported noble metal catalyst with a controllable single atom / nanocluster ratio as claimed in claim 1, characterized in that In step 2), the carrier is a metal oxide or a carbon carrier, and the metal oxide is CeO2, TiO2, MnO2, FeO x At least one of the carbon carrier is at least one of activated carbon and carbon nanotubes (CNT), and the carrier is preferably CeO2 or TiO2. The stirring time of step 2) is 2 to 10 hours.
4. The method for preparing a supported noble metal catalyst with a controllable single atom / nanocluster ratio as claimed in claim 1, characterized in that In step 2), the rapid thermal shock is performed by Joule ultrafast heating, which rapidly raises the temperature to a heat treatment temperature of 500 to 800 °C within 500 milliseconds, the heat treatment time is 10 to 600 s, and then naturally cools to room temperature.
5. The method for preparing a supported noble metal catalyst with a controllable single atom / nanocluster ratio as claimed in claim 4, characterized in that The heat treatment temperature is 550-650°C, and the heat treatment time is 20-60 s.
6. The method for preparing a supported noble metal catalyst with a controllable single atom / nanocluster ratio as claimed in claim 1, characterized in that The specific steps of step 3) are: diluting the nanocluster sol of the precious metal M with ethylene glycol, and dropping the obtained solution into the single atom catalyst while stirring evenly; then immersing at room temperature for 10-~20 hours, and then drying the sample in a vacuum oven to obtain a catalyst in which single atoms and nanoclusters of the precious metal M coexist.
7. The method for preparing a supported noble metal catalyst with a controllable single atom / nanocluster ratio as claimed in claim 1, characterized in that The molar amount of the single atoms of the noble metal M in the catalyst accounts for 10 to 50% of the total amount of both the single atoms and nanoclusters of the noble metal M, preferably 10 to 30%.
8. The method for preparing a supported noble metal catalyst with a controllable single atom / nanocluster ratio as claimed in claim 1, characterized in that The loading amount of the noble metal M in the catalyst is 0.1 ~ 0.5%.
9. A supported noble metal catalyst with a controllable single atom / nanocluster ratio prepared by the method of any one of claims 1 to 8.
10. Use of the supported noble metal catalyst with controllable single atom / nanocluster ratio as claimed in claim 9 in catalyzing CO oxidation reaction.
Citation Information
Patent Citations
Monoatomic dispersed noble metal catalyst and application thereof
CN107649124A
Alumina-loaded iridium cluster catalyst and preparation and application thereof
CN112108145A
Preparation method of metal oxide loaded sub-nanocluster and monatomic coexistence catalyst
CN115069239A
Method for regulating existence form of Rh species in rhodium-based catalyst
CN115382541A